UM in the news : marketing and promotion on social media platforms - N.A. , Hazidah; N.N. , Edzan; Y. , Mahbob; I. , Hasmawati (Persatuan Pustakawan Malaysia, 2012)
Today’s technology has made it possible for news to be disseminated in the quickest manner. Users, especially from the higher learning institutions, need to stay connected with news in order to complete some of their learning processes. The aim of this paper is to analyse the strategies used in marketing and promoting of news by the University of Malaya Library (UML). The effectiveness of these strategies will be analyzed via the number of pages viewed, shares, clicks and viral lift. The study is descriptive in nature in which it will describe the strategies used by the UML to market and promote news and also the effectiveness of these strategies. It is hoped that this study will provide some insights on the marketing and promotion of news by libraries especially at higher learning institutions.